ANALISIS KEPUASAN PELANGGAN TERHADAP KUALITAS PELAYANAN DI PT RAMAJAYA COPIER - Sudrajad JS; Nur Rahma Andayani (Politeknik Negeri Batam, 2019)
Research on customer satisfaction analysis on service quality at PT Ramajaya Copier is to analyze and determine the extent of customer satisfaction with the services provided by PT Ramajaya Copier. This research was conducted to 93 PT Ramajaya Copier customers in Batam City using the Simple Random Sampling technique. Using the method of analysis of important performance analysis (IPA) of this study resulted in 4 (four) indicators of service satisfaction statements included in quadrant I, namely improving performance to be improved to meet customer expectations. The four indicators of the statement are: employees are polite and friendly to customers (2.61), customer convenience when coming to PT Ramajaya (2.69), the company serves regardless of customer background (2.61), the company tolerates delays payment to customers (2.61).